An Experimental Investigation of the Coefficient of Discharge for Circular and Semi-Circular Weirs - O.A.Rahim, Nawzad; Mahmoud, Mahmoud I.; Rashid, Haveen M. (Sulaimani Journal for Pure and Applied Sciences, 2004)
The hydraulic characteristics of ciroular and semi-circular weirs under free flow and submerged flow conditions were studied experimentally and compared. Eighteen different weir models were tested. The first nine models were circular weirs, the rest of the models were semi-circuiar weirs. Within the range of the experiments it is shown that the weir height (p), upstrearn head over the weir(hr) . submergence ratio(h2lh1) and channel slope had significani effect on the coefficient of discharge (Cj. The results confirmed that the coefficient of discharge for circular weirs was greater that semi-circular r.veirs under free flow and submerged flow conditions, also tire va!.ue of (Co) for subrnerged flnw for both circulal and serni-cirsular weirs was l,i:rver than that at free flow condition bV(1-15)%.
Keywords: weir; coefficient of discharge; circular; semicircular; free flow; submerged flow; channel